The Values of Patient Education in Surah Ar-Rad verse 22 - Murni Yanto (Nazhruna: Jurnal Pendidikan Islam, 2021)
This research is motivated by the importance of patience in carrying out the educational process, in the world of education various problems faced by everyone are a natural thing, education must be carried out with patience because patience is a behavior of trust in Allah SWT. What are the values ​​of patient education in the Qur'an ar-rad verse 22. The hope of this research is to find out 1) How is the value of patient education in the Qur'an ar-rad verse 22, 2) The benefits of patient education in the Qur'an ar-rad verse 22, 3) The wisdom of patient education in the Qur'an Ar-Rad verse 22. The method used is library research that relies on studies and text studies. Where the researchers conducted a series of collection, managing and analyzing data taken from literature data. The data collection technique was through documentation. Based on the research that has been done, it can be concluded as follows: 1.Patience education is a very important role in dealing with problems and one way to get help from Allah SWT. 2. The benefits of patient education are: getting a reward, the heart becomes calm and always in the protection of Allah SWT. 3. The wisdom of patience, namely: making every worship more perfect and able to carry out every command and stay away from its prohibition.